Efektivitas Pengawasan Dinas Pertanian dan Pangan dalam Peredaran Daging Babi di Pasar Tradisional Kabupaten Badung - I Made Aditya Wira Sanjaya; I Nyoman Putu Budiartha; Putu Ayu Sriasih Wesna (Fakultas Hukum, Universitas Warmadewa, 2021)
In the business world, actors and consumers (use of goods or services) both have needs and interests. The business aims to earn profits and transactions with consumers, while consumers are to obtain satisfaction in terms of the price and quality of goods provided by the business actor. This study aims to explain the legal protection of consumers who consume pork in the traditional markets of Badung Regency and explain the supervision of the Government through the Agriculture and Food Service of Badung Regency on the sale of pork in the traditional markets of Badung Regency. This research used empirical legal research and a sociological legal approach. The data sources used were primary data and secondary data. Data collection techniques used in other studies used document study techniques and interviews. In this study, the processing and analysis were carried out qualitatively. This implementation is carried out at the Badung Regency Agriculture and Food Service. The rule of law against consumers is sufficient to protect consumer rights, furthermore, its effectiveness has been carried out effectively by the local government of Badung Regency